PENGARUH KOMPETENSI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU PADA YAYASAN PENDIDIKAN IMANUEL PALU - Yenny, Yenny (Katalogis, 2018)
The study aims to analyze: 1) simultaneous influence of competency, motivation, and work discipline on teachers’ performance in Immnuel Educational Foundation of Palu; 2) partial influence of competency on teachers’ performance in Immanuel Educational Foundation of Palu; 3) partial influence of motivation on teachers’ performance in Immanuel Educational Foundation of Palu; 4) partial influence of work discipline on teachers’ performance in Immanuel Educational Foundation of Palu. Type of study is quantitative descriptive. The results show that the R square value is 0.429 or 42.9% that means that independent variables of competency (X1) , motivation (X2) , and work discipline (X3) influence the performance of teachers in Immanuel Educational Foundation, Palu of 42.9% while 57.1% is influenced by other variables that are not studied. Estimation value of R is 0.655 or 65.5% that shows that competency, motivation, and work discipline influence teachers’ performance in Immanuel Educational Foundation of Palu.